The matrix reloaded: Reconstructing the boundaries between (international) law and politics. (19th September 2021) - dos Reis, Filipe; Grzybowski, Janis
Abstract: Interdisciplinary scholarship at the intersection of international law (IL) and International Relations (IR) has illuminated the roles of politics in law, of law in politics, and of the shifting boundary between the two in various areas of international affairs. The boundary itself, however, has proven resilient. While critical approaches investigating the politics of international law have come to insist on the lasting significance of legality proper, IR approaches to legalization have returned to politics. Although the apparent limits to challenging the boundary between legality and politics are not new, we suggest that they are intimately related to another great divide, i.e., that between the state and the international. Together, these two cross-cutting lines have shaped the possibilities and constraints of articulating substantive positions 'in' (international) law and politics at least since the Interwar period. Reading these distinctions as intertwined 'nested oppositions', this article reconstructs the stylized but paradigmatic debates between Max Weber and Hans Kelsen over the nature of the state and between Hans Morgenthau and Hersch Lauterpacht over the nature of the international. We further illustrate how the same conceptual oppositions still enable and constrain current debates in IL and IR, discussing as examples the creation of states and the justiciability of international crimes. Crossing and contesting the boundaries ultimately reaffirms them as the matrix in which conflicts over states and the international are articulated as legal and political.